"IMPORTANCE OF FAMILY IN PERSONAL FORMATION AND SOCIAL SUCCESS" (Universal International Scientific Journal, 2026)
In this article, the family is considered an important social environment in the process of personality formation. The family is the place of initial upbringing of a person, where the child acquires moral values, social norms and life skills. This topic highlights the role of the family in the spiritual, moral and intellectual development of a person, as well as its impact on his future social success. Parental education, a healthy environment in the family, mutual respect and support are important factors in the formation of a person as an active, responsible and successful person in society. Therefore, proper upbringing and a positive environment in the family are of great importance for the harmonious growth of a person.
Keywords: Family; personality formation; upbringing